Ego Identity Status of Medical Students in Clerkship - Beran, Tanya; Hecker, Kent; Coderre, Sylvain; Wright, Bruce; Woloschuk, Wayne; McLaughlin, Kevin (Canadian Medical Education Journal, 2011)
Background: Medical students encounter a variety of experiences that have an impact on their emerging professional identity. Clerkship, in particular, presents opportunities for students to consider their career options and decide upon a career path. The process of developing their professional identity begins well before clerkship, however. Anecdotal evidence suggests that interests in medicine begin as early as childhood. This study retrospectively examines the decision-making process clerks make in choosing medicine as a career. Methods: A total of 76 clerks (36 male, 34 female, 6 not reported) responded to four open-ended and two follow-up questions that measure career interests and pursuits. Questions addressed when and how students developed interests in medicine and alternate careers before beginning medical school. An additional eight closed questions drawn from the Ego Status Extended Objective Measure of Ego Identity Status II (EOM-EIS-II) were administered. Content analyses and inter-rater reliability analyses were conducted to classify students according to Marcia’s1 four ego identity statuses. Results: Having obtained high inter-rater consistency (Cohen’s Kappa coefficient of 0.92), responses to the open-ended questions resulted in the classification of three identity statuses. In total, 49.3% of students were in the ‘achieved’ (high exploration and commitment to choices) status and 48.1% were in the ‘foreclosed’ (low exploration but high commitment to choices) status. A small percentage (1.3%) of students were in the ‘moratorium’category (high exploration but low commitment to choices), while none of the students were in the ‘diffused’ (low exploration and low commitment to choices) category. Conclusions: With approximately half of the students demonstrating a ‘foreclosed’ status, this study reveals that despite exposure to a variety of careers when attending university, only half of the students had seriously pursued a career outside of medicine. The majority of students, moreover, developed an interest in medicine before adulthood, and did so independently from parental influence.